Peaceful Islamist mobilization in the Muslim world what went right - Chernov-Hwang, Julie (Palgrave Macmillan, 2009)
Julie Chernov Hwang presents a compelling and innovative new theory and framework for examining the variation in Islamist mobilization strategies in Muslim Asia and the Middle East.